Qualidade e conservação de manga ‘tommy atkins’ revestidas com blendas de quitosana e fécula - Celestino, Saul de Medeiros (Universidade Federal Rural do Semi-Árido, 2016)
The mango is a fruit with relatively short post-harvest shelf life even at low temperature. The use of packaging technology is promising. In this sense, the use of biodegradable coatings has advantages given that they are "environmentally correct" and can still maintain quality for longer. In view of the lack of information on the influence of coatings based on polysaccharide mixtures in maintaining the quality of mango. The present work had as objective to evaluate the quality and conservation of 'Tommy Atkins' mangoes coated with chitosan and starch blends. Mango fruits were collected at physiological maturity at stage maturation 2 and transported to the Food Technology Laboratory of UFERSA. After cleaning, weighing and identification of the mangoes, these fruits were submitted to the respective treatments and stored for 35 days, with evaluation at intervals of seven days in a refrigerated chamber at 13 ± 1ºC and 90 ± 5% RH. The experiment was conducted in a completely randomized design, in a factorial scheme, with six treatments produced from 2% cassava starch (FE) and 2% chitosan (IQ) solutions, and the treatments consisted of mixtures (T1: FE: T2: FE 3/4 and QI 1/4; T3: FE 1/2 and QI 1/2; T4: FE 1/4 and QI 3/4; T5: QI; Six storage periods (0, 7, 14, 21, 28 and 35 days) with four replications, one fruit per plot. The fruits were evaluated: loss of mass, appearance; Pulp color, firmness, soluble solids, pH, titratable acidity, SS / AT ratio, vitamin C and starch. Data were submitted to analysis of variance using SISVAR software and compared by the Scott - Knott test at 5% probability. There was a reduction in appearance, firmness, titratable acidity, ascorbic acid and starch throughout the storage. The fruits of the treatments T2, T3, T4 and T5 presented higher values of appearance, firmness, acidity, ascorbic acid and starch even with the reduction of values of these variables during storage. There was an increase in mass loss, soluble solids and SS / AT ratio during the storage period, with the lowest values observed in fruits coated with chitosan and cassava starch in the ratio ½ and ½. This also provided better conservation of the mango, ensuring a longer post-harvest life through reduced weight loss, maintenance of appearance and attributes of fruit quality
Keywords: Mangifera indica L.; Revestimentos comestíveis; Fécula de mandioca; Solução filmogênica; Quitosana; Mangifera indica L.; Edible coatings; Starch Cassava; Filogenogenic solution; Chitosan; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA